Contractor Health and Safety Compliance for Small to Medium-Sized Construction Companies - Mustapha, Zakari; Aigbavboa, Clinton; Thwala, Wellington (Boca Raton, FL : CRC Press, 2017)
"This book explores the formation of small and medium-sized construction company's (SME) compliance with health and safety issues in developing countries. Little has been written about the formation of SME contractors' health and safety compliance for developing countries, especially, in the sub-sahara regions where construction and infrastructure development activities have significantly increased in order to serve the development mandate of those countries. Thus, this book will provides insight into construction safety for SMEs, as well as health and safety compliance, and its policy implementation trends and development."--Provided by publisher.
General Introduction -- Theoretical and Conceptual Perspectives of Health and Safety Research -- Review of the Health and Safety Compliance Literature -- Construction Industry - International Literature -- Occupational Health and Safety Issues in the Nigeria Construction Industry -- Occupational Health and Safety (OHS) in South Africa -- The Construction Industry and Occupational Health and Safety in Ghana -- Research Methodology -- Results from the Delphi Study -- Conceptual Integrated Health and Safety Compliance Model for Small to Medium-Sized Construction Companies -- Survey Results -- Discussion of Results -- Conclusions and Recommendations.
Keywords: Hydrometeorology -- Remote sensing; Environmental monitoring -- Remote sensing; Droughts -- Remote sensing; Floods -- Remote sensing; Forest fires -- Remote sensing; Construction Management; Health & Safety in Construction; TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Industrial Health & Safety